2013
DOI: 10.1097/ico.0b013e3182775de4
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Eyelid Mass as an Unusual Presentation of Ocular Adnexal IgG4-Related Inflammation

Abstract: Purpose: IgG4-related sclerosing disease is a new clinicopathologic systemic entity, which can involve ocular adnexal structures, such as lacrimal glands and orbital tissues. However, this entity seems to display a more diffuse, frequently bilateral, pattern in such cases. Conjunctival involvement has not been reported in this disease. Methods:We report the case of a 67-year-old woman with left upper palpebral mass for 5 months. A biopsy was performed, and the patient underwent systemic evaluation for IgG4-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…10 Only 1 case of IgG4-RD involving the sclera 11 and 2 cases of conjunctival location of the disease have been reported: both conjunctival locations were associated with typical orbital inflammation 12 and eyelid lesions. 13 In our cases, atypical ophthalmic manifestations were the only manifestations of the disease. There were no signs of systemic or lacrymal involvement.…”
Section: Discussionmentioning
confidence: 89%
“…10 Only 1 case of IgG4-RD involving the sclera 11 and 2 cases of conjunctival location of the disease have been reported: both conjunctival locations were associated with typical orbital inflammation 12 and eyelid lesions. 13 In our cases, atypical ophthalmic manifestations were the only manifestations of the disease. There were no signs of systemic or lacrymal involvement.…”
Section: Discussionmentioning
confidence: 89%
“…Recent case reports described conjunctival involvement in patients with IgG4-related disease [6,7,8]. Here, we describe an isolated inflammatory conjunctival lesion without orbital involvement that was suggestive of IgG4-related disease.…”
Section: Introductionmentioning
confidence: 69%
“…While the lacrimal gland is the most common ophthalmic manifestation in IgG4-related disease, the conjunctiva was initially believed to be spared [4]. Recent case reports have shown conjunctival involvement in IgG4-related disease with adnexal involvement [6,8] or in isolation [7]. …”
Section: Discussionmentioning
confidence: 99%
“…Neither Sato et al nor this study had patients with IgG4-ROD originating from conjunctival or subconjunctival tissue. However, prior research suggested that IgG4-ROD can also develop at conjunctival tissue [23,24].…”
Section: Discussionmentioning
confidence: 97%